AN ANALYSIS OF CODE-MIXING USED IN “INI TALKSHOW” ON NET TV - Mahrobi Irawan; Eliwarti Eliwarti; Fadly Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to investigate the types and purposes of code-mixing used in “Ini Talkshow” You Tube videos. The research utilized a descriptive qualitative and documentation method. The source of the data in this study are from 5 “Ini Talkshow” You Tube videos entitled “Ayu Gani Valerie dan Veronika malah takut sama Om Yoo, Cie Andre malu ketauan niruin Chef Juna, Unseen Before Sule dan Nabila syok lihat pria tampan pakai sertifikat, Unseen Before Turis jauh taunya cuma modus, Unseen Before Woowww Michelle Joan klepek klepek sama gombalan Dede”which was published on 2021. The chosen videos provided with appropriate Indonesian-English code-mixing and usedto obtain the data by writing the transcript of the conversation, then a data sheet used as a secondary instrument. The data sheet takes the form of a table to record the classified information, which are displays two goals that became the study’s focus: the types and purposes of code-mixing.The result of the data analysis showed that a total of 55 instances of code-mixing within the utterances. In terms of types, 47 instances of Intra-Sentential code-mixing and 8 instances of Intra-Lexical code-mixing were found. Regarding the purposes of code-mixing, 23 utterances were categorized as fulfilling Lexical Needs, 11 utterances aimed at Being more Informative, 10 utterances were intended to assert Power, Status, and Pride, 7 utterances reflected a sense of Incompetence, 3 utterances were used for Making Jokes, and 1 utterance served the purpose of Expressing Emotion.The propensity for hosts and guest stars to engage in intra-sentential code-mixing, blending languages within words during their utterances, is notably driven by their preference for satisfying lexical requirements. The writer anticipates that these findings will yield considerable advantages by enhancing comprehension regarding code-mixing and shedding light on the reasons behind its widespread phenomenon in contemporary society.Key Word: Analysis, Code-Mixing, You Tube video, Ini Talkshow